Kajian beberapa faktor yang mempengaruhi kerentanan tanaman karet muda terhadap jamur upas - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
Study of pink fungus on rubber bark media at various age was conducted to evaluate which age of rubber tree was suitable for the fungus development. Cork layer thickness, reduced sugar and lignin contents were studied to justify the influencing factor of the plant resistance to pink fungus. Vegetative development of pink fungus on rubber bark agar media was studied by in vitro. Observations were measurements of colony diameter and dry weight of mycelia. Reduced suger content was analyzed using spectrofotometri by NelsonSomogyi and lignin content was observed by extraction method by Jennin-Isherwood. Measurement of cork layer thickness was done using section method and ocular micrometer mounted on light microscope at 450 X magnification. Colonies diameter and dry weight mycelia of 10-days old pink fungus were highest on 5- year old rubber bark media, lower on 3-, 7- and 10- year old, and lowest on one year old. On 3 to 7- year-old rubber tree media, colonies of pink fungus were thick. It means that rubber bark of 3 to 7 years of age were succeptible to pink fungus. Reduced sugar content of 3 up to 7 years old bark was not related to plant succeptibility against pink fungus. Lignin content of 3 up to 7 years old rubber bark was low. Increase of cork layer of 3 to 7 years old rubber tree caused some cracks at epidermis which were susceptible to pink fungus.